Growth performances, carcass yield and meat quality of free range village chickens fed on diet containing dehydrated processed food waste - Shanaghi, Hossein (2015)
The study was conducted to evaluate effects of feeding diets containing dehydrated processed food wastes (DPFW) on growth performances (feed intake, body weight gain, feed conversion ratio), meat quality and carcass yield of free range village chickens for 10 weeks. The food waste was collected from 20 different restaurants of Universiti Putra Malaysia during 3 months. The first step of processing food waste was reducing the fat content of food waste by soaking it in hot water at >90 °C - < 100 °C for 10 minutes. Then it was dehydrated under the sun (3 days) (average 30 °C), mixed and the representative samples were analyzed for dry matter (DM) 89.3%, crude protein (CP) 16%, ether extract (EE) 7.1%, crude fiber (CF) 3.7%, crude ash 7.4%, NaCl 3.07%, Ca 1.56%, phosphorous 0.87% and ME 3700 kcal/kg. The formulated diet was based on chemical composition of DPFW. The experimental design used was completely randomized design involving four different rations. The rations contained processed dehydrated food waste at the rate of 0 (T1), 20 (T2),40 (T3) and 60% (T4). 180 grower female village chickens at four weeks of age with average initial body weight 300±10g (mean ± SD) were randomly distributed to four treatments with three replicates (15 birds per replicate) for grower and finisher rearing periods (grower 5-9 weeks and finisher 10-14 weeks). The four treatment rations formulated were approximately iso-caloric and iso-nutrigenous with 3000 kcal/kg ME and 20% CP for grower period and 3100 kcal/kg ME and 18% CP for finisher period, respectively. As the data suggested, the differences in growth performances of village chickens among treatments may be related with the composition and/or the levels of DPFW intake. Accordingly, the results showed that the highest feed intakes in grower (634 g) and finisher phases (2722.1) were observed in the control group, while the lowest was in treatment 4 (586.3 g for grower and 2542.6 g for finisher phases) (P<0.05). No significant difference was found between the control group (634 g and 2722.1g) and treatment 2 (630.7g and 2707g) in grower and finisher phase (P>0.05). Linearly declines in body weight gain were recorded in diets containing more than 20% of DPFW during both grower and finisher rearing phases. Higher amounts of DPFW in the diets (more than 20%) reduced the intake of nutrients and metabolic energy. Consequently, birds grew significantly less compared with those in the control group. The average FCR showed no significant (P>0.05) differences among birds fed on just commercial feedstuff in the control group (3.52) and treatment 2 (3.55) containing 20% processed food waste during whole rearing period. Feed conversion ratio was poor and significantly in treatment 3 (3.65) and treatment 4 (3.69) (P<0.05). DPFW inclusion showed no significant differneces (P>0.05) on the carcass weight, dressing percentage, relative weights of the heart, liver and intestine when T2 (20% DPFW) was compared to the control group. However, by increasing the amount of DPFW on the diets (40% and 60%) significant differences were observed in all items in T3 and T4 compared to the control group (P<0.05). In addition, a significant interaction between DPFW and feed intake (P<0.05) resulted in a higher reduction in carcass yield of birds consuming more than 20% DPFW when compared with birds without access to DPFW. pH value of T4 did not show a significant difference from T3 (P>0.05), while it showed a significant difference between T2 and the control group (P<0.05). This trend was similar to L value and a value, whereas no significant differences observed in b value among treatments (P>0.05). Shear value was slightly higher in control group (p<0.05) compared with other treatments. However, no significant differences were recorded in all treatments (P>0.05). Although cooking loss in T4 was slightly higher than other treatments, there were no significant differences among all treatments (P>0.05). Fat content and ash were the lowest in the control group while moisture was the highest (71.14 %). T4 significantly had the highest fat content and it decreased linearly to the control group (P<0.05). Crude protein was slightly higher in the control group compared with other treatments, however, no significant differences were found (P>0.05). The present study showed that the feeding diet containing DPFW resulted in significantly lower drip loss and higher pH in free-range village chickens meat. This may be attributed to the lower glycogen content of the muscles and decreased lactic acid (LD) production. The predominant fatty acids in meat for all treatments were saturated fatty acids; palmitic acid (16:1), strearic acid (18:0), the mono-unsaturated fatty acid palmitic acid (16:1) and oleic acid (18:1n-9), and the polyunsaturated fatty acids (PUFA); linoleic acid (18:2n-6) and arachidonic acid (20:4n-6). The total saturated fatty acid (SFA) was the highest in T4 (40.28%), followed by T3 (36.78%), T2 (33.68%) and T1 (30.16). In contrast, the total polyunsaturated fatty acid (PUFA) was the lowest in T4 (26.82%), followed linearly by T3 (30.0%), T2 (32.91%) and T1 (36.05%). Furthermore, the ratio of PUFA/SFA in treatment 4 (60% DPFW) was the lowest, representing (0.66%) and it increased respectively from T3 (0.81%), and T2 (0.97%) to T1 (1.19%). The highest total n-6 were found in T1 (34), while the lowest belonged to T4 (24.35%). However, the highest total n-3 belonged to T4 (2.47%), whereas the lowest one belonged to the control group (2.05%). Consequently, the inclusion of more than 20% DPFW, had a major influence on the fatty acid composition of chicken meat, leading to a significant decrease in most PUFA, increase saturated fatty acid (SFA) content of chicken meat and n-6/n-3 ratio. In general, the village chicken fed on a diet containing DPFW contained fat with a greater proportion of SFA than the control group. According to a sensory evaluation result, there were no significant differences in tenderness, juiciness, color or flavor of village chicken meat among all treatments (P>0.05). However, the descriptive panel found some significant differences (P<0.05) in texture and overall acceptability (P<0.05). As the result of sensory evaluation shown, overall liking in texture of chicken meat in the control group was the highest (6.8) while in T4 was the lowest (6.26). As panelists preferred, chicken meat from T4 (60% DPFW) had the highest liking rate of 6.6 (P<0.05) while the last one was control group (0% DPFW) with the rate of 6.06 (like slightly) (P<0.05). Furthermore there was no significant difference between T3 (40% DPFW) (6.4) and T2 (20% DPFW) (6.26) (P>0.05). The data presented, suggests that diets containing dehydrated processed food wastes had positive effects on tenderness, juiciness and flavor of meat, even though there were no significant differences among all treatments (P>0.05). According to the results, it seems that diets containing up to 20% dehydrated processed food waste could be used in grower and finisher rearing phases without any negative effects on growth performances, carcass yield and meat quality of free range village chickens.